Are the Effects of Cognitive Behavior Therapy for Depression Falling? Review and Critique of the Evidence. (June 2016) - Waltman, Scott H.; Creed, Torrey A.; Beck, Aaron T.
Abstract : Johnsen and Friborg ( Psychological Bulletin 2015; doi:10.1037/bul0000015 ) report that modern cognitive behavior therapy (CBT) clinical trials yield less relief from depression compared to seminal trials, but methodological limitations may qualify the conclusions. Given the empirical support for CBT for depression, a closer look is warranted. High I 2 coefficients were reported for a subgroup analysis, and no heterogeneity estimates were reported for the primary analyses, raising concerns about the appropriateness of meta‐analysis and interpretations of the findings. Concerns are raised about the presence of CBT in comparison groups. Data regarding CBT competence were largely missing, and fidelity data were often absent. Without these data, attributions about changes in effect sizes from early studies may be premature. The proliferation of CBT may have been accompanied by modifications to the model, accompanied by variability in quality, adherence, and competence. A call to high‐fidelity and high‐quality CBT is made.